Effect of metal oxide nano-particles addition on physical properties of hydroxyapatite - N. Lertcumfu (2018)
In the present study the effects of metal oxide nano-particles addition on the microstructure, physical properties of the HA ceramics were investigated. Many techniques were used for the analysis. X-ray diffraction analysis revealed a co-exist phases between hydroxyapatite and tricalcium phosphate in the sintered samples. Addition of NiO resulted an increase in the lattice parameters of the tricalcium phosphates due to the bigger radii atom (Ni) substitution for the small radii atom (Ca). Energy dispersive spectroscopy suggested that most of NiO particles located at grain boundary, resulting in an improvement of hardness of the samples. © (2012) Trans Tech Publications.